2014
DOI: 10.2139/ssrn.2507368
|View full text |Cite
|
Sign up to set email alerts
|

Can Trustworthiness in a Supply Chain Be Signaled?

Abstract: The relationship between a buyer and its suppliers is important and often relies on factors beyond the terms of a contractual agreement. Buyers can therefore benefit from identifying trustworthy suppliers. We argue that pre-contractual actions by the supplier, for example making costly buyer-specific investments without a long-term contract, can signal a supplier's trustworthiness. We develop a theoretical model to reflect supplier trustworthiness, and identify when a buyer can benefit from identifying trustwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…We also enrich this line of research by revealing the equivalence between mutual commitments and a weighted sum form of utility, a utility embedded in social preference (Beer et al. ). To our knowledge, this finding is new to the literature.…”
Section: Literature Reviewmentioning
confidence: 93%
“…We also enrich this line of research by revealing the equivalence between mutual commitments and a weighted sum form of utility, a utility embedded in social preference (Beer et al. ). To our knowledge, this finding is new to the literature.…”
Section: Literature Reviewmentioning
confidence: 93%
“…We have also accumulated evidence to better predict how trust in supply chains may be affected by environmental and institutional factors. For example, financial vulnerabilities and market uncertainty are barriers to trust; competition can impede trust, and making relation-specific investments without a binding agreement signals trustworthiness and engenders trust from supply chain partners (Özer et al 2011, Spiliotopoulou et al 2016, Beer et al 2018). In the meantime, factors of trust and trustworthiness are being incorporated in traditional OM models to more accurately predict behavior and better prescribe managerial strategies (Özer et al 2011, Ebrahim-Khanjari et al 2012, Scheele et al 2018.…”
Section: The Case Of Supply Chain Information Sharingmentioning
confidence: 99%
“…Qin et al [23] demonstrated the transmission mechanism of the retailer’s fairness-concern information with signaling game and analyzed the existing of the separating equilibrium and pooling equilibrium under asymmetric information. Beer et al [24] showed that the buyer-specific investment can be used as a signal of trustworthiness and that the supply chain performance improves when the trustworthiness of suppliers can be identified. There is relatively little literature pointing to signaling game in low-carbon supply chain and it mainly focuses on non-low carbon issues research.…”
Section: Literature Reviewmentioning
confidence: 99%